Immunopathogenesis pathways of primary immune thrombocytopenia: a comprehensive overview - Al-Kaabi, Zaman I. L. (Pharmakeftiki, 2025)
Primary immune thrombocytopenia (ITP) is an autoimmune disorder characterized by both the destruction and impaired production of platelets. Mucocutaneous bleeding is the predominant symptom in patients with severely reduced platelet counts. The pathogenesis of ITP involves complex immune mechanisms initiated by aberrant T cell responses and the action of splenic T follicular helper cells, which activate autoreactive B cells. These B cells produce anti-platelet autoantibodies that promote platelet phagocytosis by macrophages; the primary antigen-presenting cells in ITP. Additionally, enhanced cytotoxic T-cell activity induces platelet apoptosis, further contributing to thrombocytopenia. Immune-mediated targeting of megakaryocytes, along with reduced levels of thrombopoietin (the principal growth factor for megakaryocyte maturation) results in dysfunctional bone marrow platelet production. This review outlines the immune mechanisms driving ITP and elucidates the roles of immune cells in both platelet destruction and impaired production.